The punchline of "The Joke": the impact of process corruption in the Queensland Police Force, 1957-1987 - Bleakley, Paul (2019)
The Queensland Police Force became virtually synonymous with corruption in the aftermath of the Fitzgerald Inquiry, a judicial examination of police misconduct in that state that took place between 1987 and 1989. While many of the Fitzgerald Inquiry’s findings related to the illicit involvement of police with organised crime, this thesis proposes that it was in fact process corruption that had the greatest impact on the enforcement of law and order in Queensland in the thirty years from 1957 to 1987. It explores process corruption in a variety of forms, from excessive force to the fabrication of evidence, and makes the case that the Queensland Police Force was routinely reliant on procedural misconduct to assert its authority over the community. The thesis examines the way process corruption was exercised against several vulnerable subpopulations in Queensland, including the LGBTQI community, young people, and the protest movement. In doing so, it exposes a systemic pattern of enforcement where process corruption was both tolerated and encouraged by senior police and the conservative government that presided over Queensland in this era.